Growing and X-ray diffraction pattern of single-crystal double phosphate Li₂Mn(PO₃)₄ - Nagorny, P.G.; Slobodyanik, N.S.; Lavrik, R.V.; Ushchapivska, T.I. (Functional Materials, 2018)
Optimum conditions for the growing of single crystals of Li₂Mn(PO₃)₄ compound have been selected. Complete X-ray diffraction analysis has been performed to study synthesized phosphate Li₂Mn(PO₃)₄. According to its structure, the double phosphate belongs to the orthorhombic crystal system, space group Pnma; lattice parameters are the following: a = 9.268(1), b = 9.421(1), c = 10.088(1), V = 880.93, Z = 4, ρcalc. = 2.901 g/cm3. Structural features of the synthesized phosphate have been determined. The compound has been studied using DTA and IR spectroscopy techniques along with the complete elemental analysis.